Apresentação da música não contingente anterior à iniciação de estereotipias vocais em crianças com Transtorno do Espectro do Autismo - Molina, Perolayne Bueno (Universidade Federal de São Carlos, 2021)
Vocal stereotypies have been described in behavioral literature as repetitive responses to any words or sounds, usually maintained by automatic reinforcement, often presented by individuals within the Autism Spectrum Disorder. In several situations, vocal stereotypy can be considered a problem-behavior, as it can harm the learning environment of both those who perform it and those around them. Access to non-contingent music (NCM) has been used to reduce such responses in view of the effective results of this procedure in reducing these stereotyped vocalizations. In contrast to the possibility of accidentally reinforcing unwanted responses through the use of NCM, the implementation of momentary differential reinforcement of zero responses (MDRO) can be useful, avoiding this problem. This research aimed to verify the effects of a procedure that provides access to non-contingent music (NCM) added to a zero-response differential reinforcement (MDRO) procedure in the reduction of vocal stereotypies in two children with ASD, in their home environments . Data analysis was performed in order to compare the frequency of vocal stereotypies under the conditions: (i) LB and (ii) NCM+MDRO. For this, the ABAB Reversal Design was used. The results showed that during the intervention sessions the levels of vocal stereotypies decreased while the engagement in toy manipulation responses increased for both participants. For one of the participants, there was, on average, a decrease in the percentage of time engaged in vocal stereotypies from 74% in LB to an average of 8.6% during the NCM+MDRO sessions; that is, a 65.4% decrease with the introduction of VI. For the other participant, the average total percentages of time engaged in stereotyping in LB sessions was 67% and dropped by almost half to 35.2%. The study discusses the maintenance functions of these decontextualized vocal responses and whether music, as an auditory reinforcing stimulus, when provided in a time scheme, could have altered the Motivational Operations to the engagement of participants in these stereotyped vocal responses.
Presentation of non-contingent music before the initiation of vocal stereotypes in children with Autism Spectrum Disorder
Keywords: Estereotipia vocal; Música; Reforçamento não-contingente; Autismo; Vocal stereotypy; Music; Non-contingent reinforcement; Autism; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::TECNOLOGIA EDUCACIONAL; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL